PROPUESTA DE CREACIÓN DE UN BANCO COMUNAL PARA LAS COOPERATIVAS DE TRANSPORTE PÚBLICO DE LA CIUDAD DE PORTOVELO - PROVINCIA DE EL ORO SUPERVISADAS POR LA SUPERINTENDENCIA DE ECONOMÍA POPULAR Y SOLIDARIA - Granda Aguilar, Arelí Verenice (2019)
The present work aims to provide an alternative solution to the savings and credit needs of members of public transport cooperatives in the city of Portovelo regulated by the Superintendency of Popular and Solidarity Economy through the creation of a financial institution that provides financial services to improve the performance of their activities and in turn encourage a culture of savings by creating their own source of economic resources. It is based on fulfilling three specific objectives, such as Market Study, Technical Study, Legal and Financial Administrative Study. In order to comply with the objectives set forth in the investigation, the methodology applied to an investment project with its respective adaptations was taken as a base, using methods and techniques according to the objectives formulated among them the scientific, inductive, deductive, statistical analytical method and techniques such as direct observation, surveys and bibliographic compilation. Through which information was collected which was treated statistically allowing to obtain values for analysis and reach different conclusions. In this way, the results obtained from the market study in which a survey was applied to the members of the cooperatives made it possible to establish the interest and degree of acceptance of the communal bank, as well as the products and services it will offer. The exact number of members willing to belong to the institution was determined, that is to say, the effective demand, as well as the amounts they would contribute to the formation of the initial capital and monthly savings. The technical study also determined the exact location of the Banco Comunal, which will be in one of the headquarters of the transport cooperatives that are part of this study, the demand for loans to cover, the material and human requirements as well as the processes to follow for the provision of services of the communal bank; the legal administrative study designed the business philosophy of the institution, the organic and functional structure, the statutes and regulations that will govern the bank. For the development of the financial study it was considered the investment of the project the same one that will be covered with contributions of the partners, the costs, income and flow of cash, after this methodologies were applied for the calculation of financial indicators and of profitability that allowed to calculate the Net Present Value that turned out to be positive, the Internal Rate of Return higher to the expected one, the Ratio Benefit 5 Cost is within the established parameters and the Period of Recovery of Capital is given within the term of evaluation of the project. Finally, the proposal for the creation of a communal bank for the public transport cooperatives of the city of Portovelo supervised by the Superintendence of Popular and Solidary Economy is financially feasible and represents an economic growth for the members.